gga-miR-155 Enhances Type I Interferon Expression and Suppresses Infectious Burse Disease Virus Replication via Targeting SOCS1 and TANK - Wang, Bin; Fu, Mengjiao; Liu, Yanan; Wang, Yongqiang; Li, Xiaoqi; Cao, Hong; Zheng, Shijun J. (Frontiers in Cellular and Infection Microbiology, 2018)
Infectious bursal disease (IBD) is an acute, highly contagious, and immunosuppressive avian disease caused by IBD virus (IBDV). MicroRNAs (miRNAs) are involved in host-pathogen interactions and innate immune response to viral infection. However the role of miRNAs in host response to IBDV infection is not clear. We report here that gga-miR-155 acts as an anti-virus host factor inhibiting IBDV replication. We found that transfection of DF-1 cells with gga-miR-155 suppressed IBDV replication, while blockage of the endogenous gga-miR-155 by inhibitors enhanced IBDV replication. Furthermore, our data showed that gga-miR-155 enhanced the expression of IFN-β in DF-1 cells post poly(I:C) stimulation. Importantly, we found that gga-miR-155 enhanced type I interferon expression via targeting SOCS1 and TANK, two negative regulators of type I IFN signaling. These results indicate that gga-miR-155 plays a critical role in cell response to IBDV infection.